Effect of date of planting and rainfall distribution on the yield of five cassava varieties in Lampung, Indonesia - Fauzan, Ir; Puspitorini, Palupi (International Center for Tropical Agriculture, 2001)
Improved cassava varieties have been widely disseminated to farmers in Lampung and this has resulted in substantial economic gains to both factories and farmers. But, considering that the rainfall distribution in Lampung province is not uniform and that there is a prolonged dry period about every three years, it is important to know the response of each variety to drought during its growth cycle. In this way, varieties with greater drought tolerance can be selected before being disseminated to farmers and planted throughout the year. Thus, an experiment was conducted to study the effect of dry periods during different stages of the growth cycle on cassava yield and starch production of five selected varieties in Umas Jaya Farm (UJF). Five selected varieties, i.e. Adira 4, Rayong 60, Rayong 90, Kasetsart 50, and CMR30-56-1, were planted in plots with an effective plot size of 0.1 ha, without replication. Subplots of each variety were planted every month starting in July, 1996. At harvest, fresh root yields and root starch contents (using the Reimann scale) were determined, and from those starch production was calculated. The effect of planting dates and rainfall on the root yield, starch content and starch yield of the various varieties showed a decrease in root yield when the crop was subjected to a dry period, defined here as a period of two or more months with less than 100 mm rainfall; the decrease ranged from 14.88 t/ha for Kasetsart 50 to 20.11 t/ha for Rayong 60. Without a dry period during the growth cycle, the average fresh root yields did not differ significantly among varieties, ranging from 38.39 to 44.02 t/ha. The average starch content was higher without than with a dry period. However, in four of the five varieties (Kasetsart 50 being the exception) the highest starch content was observed when cassava was subjected to two or three dry months just prior to harvest. Average starch yields of all varieties were reduced by about 50% when plants were subjected to a dry period during the growth cycle, as compared to those receiving uniform rainfall without a dry period. When subjected to drought stress, the lowest starch yield was obtained with Adira 4, and the highest with CMR30-56-1. In conclusion, when subjected to a long dry period during the growth cycle, both the fresh root yield and starch yield of all tested varieties decreased. But, under non-uniform rainfall distribution, the fresh root yields of Rayong 60, Kasetsart 50 and CMR30-56-1 were much higher than that of Adira 4, and the starch yields of all four varieties were also higher than that of Adira 4. Under uniform rainfall distribution, starch yields of Rayong 90, Kasetsart 50 and CMR30-56-1 were higher than those of Adira 4 and Rayong 60. A dry period from the 3rd to the 8th month after planting is the most critical in reducing both the root and starch yields as well as the starch content of all tested varieties